2020
DOI: 10.1016/j.sjbs.2020.09.013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of growth regulator Tytanit dose on Medicago x varia T. Martin and Trifolium pratense L. yield and nutritional value

Abstract: The aim of the research was to evaluate the effect of foliar application of different doses of Tytanit as a biostimulant on the yield and nutritional value of Medicago × varia T. Martin and Trifolium pratense L. It was assumed that titanium application during any life cycle of alfalfa hybrid and red clover would contribute to their growth, digestibility, and total protein content. In addition, it was expected that increasing doses of Tytanit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The results showed that the average value of dry matter digestibility in Festulolium was 62.61% and did not fully meet the above standard set by Stachowicz [43]. Slightly lower digestibility of Tytanit-treated plants were recorded by Sosnowski et al [6], with 57.7% for Trifolium pratense and 55.5% for hybrid alfalfa.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The results showed that the average value of dry matter digestibility in Festulolium was 62.61% and did not fully meet the above standard set by Stachowicz [43]. Slightly lower digestibility of Tytanit-treated plants were recorded by Sosnowski et al [6], with 57.7% for Trifolium pratense and 55.5% for hybrid alfalfa.…”
Section: Discussionmentioning
confidence: 91%
“…They are applied to the soil as soil conditioners or to leaves. An example of one such product is Tytanit, containing titanium [4][5][6][7]. Tytanit contains 8.5 g dm-3 of the chelated form of titanium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence indicates that titanium ions have plant growth-regulating activity ( 15 17 , 19 ). Our previous study showed that titanium ions could improve the expression of genes related to photosynthesis, protein translation, and disease resistance in Medicago sativa ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that titanium ions can promote crop growth and development by stimulating specific enzyme activities and increasing chlorophyll content and photosynthesis ( 16 ). A commercial fertilizer containing titanium, Tytanit, can improve crop yield and quality ( 17 ). Additionally, titanium can degrade organic pesticides and herbicides in soil by redox reactions and photocatalysis ( 18 ); it can also inhibit bacterial growth and extend the vase life of cut flowers ( 19 ).…”
Section: Introductionmentioning
confidence: 99%